The development of a web-based claims system - Syed Zulkarnain, Syed Idrus; Ahmad Zulhusni, Rozali; Hazry, Desa, Prof. Madya Dr. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/